The effect of different forms of dysglycemia during pregnancy on maternal and fetal outcomes in treated women and comparison with large cohort studies - Soliman, Ashraf; Salama, Husam; Al Rifai, Hilal; De Sanctis, Vincenzo; Al-Obaidly, Sawsan; Al Qubasi, Mai; Olukade, Tawa (Acta Biomedica Atenei Parmensis, 2018)
Aims of the study: We describe the impact of different forms of dysglycemia on maternal and neonatal health. This research is a part of the PEARL-Peristat Maternal and newborn registry, funded by Qatar National Research Fund (QNRF) Doha, Qatar. Methods: A population-based retrospective data analysis of 12,255 women with singleton pregnancies screened during the year 2016-2017, of which 3,027 women were identified with gestation diabetes mellitus (GDM) during pregnancy and 233 were diabetic before pregnancy. Data on maternal outcome was collected from the PEARL-Peristat Maternal and newborn registry. Results: The prevalence of GDM and diabetes mellitus (DM) was 24.7 % and 1.9%, respectively. 55% of DM, 38% of GDM and 25.6% of controls were obese (p